2019
DOI: 10.1371/journal.pone.0225222
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo perfusion-based engraftment of genetically engineered cell sensors into transplantable organs

Abstract: Cellular rejection of liver transplant allografts remains a concern despite immunosuppressant use. Existing transplant biomarkers are often not sensitive enough to detect acute or chronic rejection at an early enough stage to allow successful clinical intervention. We herein developed a cell-based sensor that can potentially be used for monitoring local events following liver transplantation. Utilizing a machine perfusion system as a platform to engraft the cells into a donor liver, we effectively established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Although they did not study the effect of NMP combined with BMMSCs on the kidney, they confirmed the feasibility of NMP combined with BMMSCs. In another study, researchers used NMP to perfuse genetically engineered cell sensors into the liver and showed that the engineered cells could colonize the liver, thus suggesting that this technique could be used to monitor liver status [22]. These studies confirmed the feasibility of NMP combined with cell therapy and also demonstrated the feasibility of modifying cells for organ protection in vitro.…”
Section: Introductionmentioning
confidence: 87%
“…Although they did not study the effect of NMP combined with BMMSCs on the kidney, they confirmed the feasibility of NMP combined with BMMSCs. In another study, researchers used NMP to perfuse genetically engineered cell sensors into the liver and showed that the engineered cells could colonize the liver, thus suggesting that this technique could be used to monitor liver status [22]. These studies confirmed the feasibility of NMP combined with cell therapy and also demonstrated the feasibility of modifying cells for organ protection in vitro.…”
Section: Introductionmentioning
confidence: 87%
“…Second, the mitochondrial redox response after ischemia was significantly different between the mild and severe ischemic livers in the left lateral lobe but the same in the right medial lobe. Indeed literature reports better perfusion of the right medial lobe in anatomical and physiological studies [ 53 55 ]. From a practical perspective, this observation demonstrates the significance to account for spatial differences in viability assessment of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of NMP experience with those livers, it is hard to predict the viability rate among those, though it is likely less than 55% given the slightly higher DRI of that cohort. This cohort may reflect severely injured grafts that would not respond to conventional short-term NMP but may benefit from longer-term perfusion strategies, 20 adjunct therapeutics aimed at graft rehabilitation, [21][22][23] or techniques that avoid additional ischemic injury such as ischemia-free LT. 24 Although a portion of the discarded livers in the perfused co- for graft acceptance, such as donor age over 50 or total WIT over 30 minutes, are likely to be de-emphasized with improvements in objective viability assessment 27 and as experience with transplantation of NMP grafts increases. 7,9,11,28 Moreover, NMP would deescalate the time-sensitive race to match, locate, and prepare a recipient for the operating room, especially in situations of rapid DCD procurement or last-minute organ offers.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of NMP experience with those livers, it is hard to predict the viability rate among those, though it is likely less than 55% given the slightly higher DRI of that cohort. This cohort may reflect severely injured grafts that would not respond to conventional short‐term NMP but may benefit from longer‐term perfusion strategies, 20 adjunct therapeutics aimed at graft rehabilitation, 21‐23 or techniques that avoid additional ischemic injury such as ischemia‐free LT 24 …”
Section: Discussionmentioning
confidence: 99%